Reliability of the Evidence to Guide Decision-Making in Acupuncture for Functional Dyspepsia - Huang, Jinke; Liu, Jiali; Liu, Zhihong; Ma, Jing; Ma, Jinxin; Lv, Mi; Wang, Fengyun; Tang, Xudong (Frontiers in Public Health, 2022)
Background and Aims There has been a significant increase in the number of systematic reviews (SRs)/meta-analyses (MAs) investigating the effects of acupuncture for functional dyspepsia (FD). To systematically collate, appraise, and synthesize the current evidence, we carried out an umbrella review of SRs/MAs. Methods Systemic reviews/meta-analyses on acupuncture for FD were collected by searching major medical databases. The included studies were evaluated in terms of methodological quality, reporting quality, and evidence quality using the criteria from the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2) tool, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, and the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) system, respectively. Results Ten SRs/MAs were analyzed for this study. The methodological quality, reporting quality, and evidence quality of the included SRs/MAs were generally unsatisfactory. Lack of protocol registration, no list of excluded trials, or lack of a comprehensive search strategy were the main limitations. No high-quality evidence was found to support the effects of acupuncture for FD; the qualitative data synthesis relied on low quality trials with small sample sizes and was the main factor for evidence degradation. Conclusions Acupuncture seems to have a promising efficacy in the treatment of FD. It provides a new and prospective therapeutic method for FD. Although the quality of the included SRs/MAs was generally low and defects were frequent, this umbrella review highlights areas where improvement in methodology is required.